Synthesis and Curing of New Phenolic Resins Containing Pendant TetrachloroPhthalimides - Al-Azzawi , Ahlam Marouf; Yaseen , HibaKhadim (Iraqi Journal of Science, 2022)
Four new phenol-formaldehyde resins containing tetrachlorophthalimides in their repeating units were synthesized via condensation of formaldehyde with N-(hydroxy phenyl)tetrachlorophthalimides under conditions similar to those used in novolac preparation. In this work structural modifications were performed first via design and synthesis of new phenolic component represented by phenolic ring linked to thermally stable tetrachlorophthalimide moiety which condense with formaldehyde and second via introducing of phenolic hydroxyl groups present in the new synthesized resins by esterification reaction with acetyl chloride producing the corresponding acetoxy substituted resins. Both the prepared and the cured resins have new properties which may serve different applications.